Microstructural Characterization of a Cr–Mo–W–Co Hot-Work Die Steel After Tempering - Ha, Seong-Ho; Shin, Young-Chul; Lim, Sung-Hwan (Archives of Metallurgy and Materials, 2026)
The microstructural characteristics of a Cr–Mo–W–Co hot-work die steel subjected to tempering were systematically investigated using scanning electron microscopy (SEM), electron backscatter diffraction (EBSD), and transmission electron microscopy (TEM). All analyses were conducted under a unified tempering condition of 580°C for 6 h in order to establish a coherent interpretation of the stabilized microstructural state. SEM observations revealed the presence of micrometer-scale bright particles whose size and distribution remained unchanged after tempering, indicating that they are pre-existing carbides rather than tempering-induced precipitates. EBSD analysis showed a pronounced change in local crystallographic substructure after tempering, as evidenced by an increase in kernel average misorientation, suggesting sub-grain scale rearrangement within the matrix. TEM and selected area electron diffraction confirmed the formation of crystalline precipitates with well-defined interfaces, which could not be resolved by SEM. STEM-EDS analysis further demonstrated that these precipitates are Mo–W-rich complex alloy carbides incorporating multiple alloying elements.